FAIR PROFIT DISTRIBUTION IN DELIVERY SERVICE COLLABORATION CONSIDERING SERVICE QUALITY - Makhmudov, Muzaffar; Lee, Gyu M.; Ko, Chang Seong (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
Electronic commerce (e-commerce) transactions have become quite prevailing over the last decade. Due to the COVID-19 pandemic, consumers have started to make more online purchases, using fast electronic payment and transaction methods. This trend has led to a surge in sales-to-consumers (B2C) and inter-enterprise (B2B) e-commerce. The express or last-mile parcel delivery business of large companies such as Amazon, Alibaba, or Coupang has grown fast, and their market share has risen while the small and medium-sized delivery companies continue to struggle to survive. While anticipation of further growth in e-commerce at rapid rates is still there, small and medium-sized delivery companies shall always look for ways to remain competitive. Collaboration with other companies is a way of their survival in rapid market competition. In general, parcel delivery companies handle and deliver various types of items or products, which are usually mixed in volume, and some require special facilities. Additionally, there are unforeseen troubles during the delivery process, such as loss, damage, or delay, which may quickly reflect the delivery company's reputation and service reliability. When a collaborative delivery system is in place, the frequency of delivery troubles may increase due to differences in delivery processes among participating delivery companies, especially when these participants handle different types of items: regular, oversized/overweighted, and refrigerated items. This study aims to consider defective rates in the delivery service of participating companies and impose a penalty for such defects if any. The multi-objective programming model is proposed to describe the problem considering the delivery by types, defective rate, and penalty) while the collaboration group's profit and individual incremental profit of each participating delivery company can be maximized. The max-sum criterion, max-min criterion, Shapley value allocation, and nucleolus-based allocation methods are used to find an optimal solution and fair profit distribution for the collaboration group. Finally, the effectiveness of the proposed model is demonstrated through an illustrative numerical example.